Active Verb Spell Checking Mem- + P in Indonesian Language Using the Jaro-Winkler Distance Algorithm - Anggoro, Dimas Aryo; Nurfadilah, Inayah (Iraqi Journal of Science, 2022)
The Indonesian language is used as a means of communication, including written communication. Unfortunately, many mistakes are found in Indonesian language writing, such as the writing of active verbs with the prefix mem- followed by the letter P. This problem can be addressed with the spell-checking method. Spell checking is a process in computer programs to check the spelling of each word in electronic text or documents in the correct order. To better the active verb this study used the Jaro-Winkler Distance algorithm. Meanwhile, for system development, the Iterative Waterfall method was used. The system output is active verbs of mem- + P which is standardized according to the Great Dictionary of the Indonesian Language of the Language Center (KBBI) and the morphological rules of the Indonesian Language Spelling System. The accuracy value of the algorithm was 80% for common mistakes, 95% for specific mistakes, and 80% for correctable mistakes with word suggestions.